Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus